“No country, this, for old men”: A View of the Aging Artist through Intertexts in J. M. Coetzee’s Disgrace - Reichmann, Angelika (Hungarian Journal of English and American Studies, 2020)
J. M. Coetzee’s Disgrace (1999) features two emblematic modernist representations of the aging artist, William Butler Yeats’s “Sailing to Byzantium” and T. S. Eliot’s “The Love Song of J. Alfred Prufrock,” which have not been given enough critical attention. Focusing on the Romantic notions underlying David Lurie’s worldview, current critical discourse, with the notable exception of Mike Marais, suggests that Lurie’s career follows the patterns of the Bildungsroman. Taking its cue from Marais, the present intertextual reading discusses Lurie’s “anti-Bildungsroman” in the light of the novel’s non-Romantic intertexts. It argues that they highlight, on the one hand, Lurie’s chiastic thought-processes, which are likely to bracket any progress or development. On the other hand, they reveal his (self)-ageism and the entrenched ageism of the literary tradition he relies on. Those, in turn, also give a pessimistic prognosis of his discovering a protective discourse or worldview which would allow him—and post-apartheid South Africa—to “age gracefully.” Likewise, they manifest yet another aspect of the novel’s unreliable narration, which—unlike Lurie’s sexism and racism—is rooted in so universal fears that, instead of alienating readers from his perspective, it makes his bleak  vision of post-apartheid South Africa even more compelling. (AR)